Buckling Behavior of Poly-Phenylene-Sulfide/Carbon L-Shaped Stringers and a Stiffened Panel Obtained by Induction Welding - Scarselli, Gennaro; Pappadà, Silvio; Buccoliero, Giuseppe; Maffezzoli, Alfonso (Frontiers in Materials, 2020)
Although the high performance thermoplastics matrix composites have been studied for more than thirty years, only recently their advantages have been properly perceived and exploited, for a wide range of applications either in secondary either in primary aeronautical structures. In this work, compression testing of a flat panel stiffened with L-shaped stringers made of Polyphenylene-sulfide (PPS) matrix reinforced with carbon fibres, is presented. The stiffeners were joined to the base plate by induction welding, as reported in a former study. The numerical activities, aimed at static, buckling and post-buckling analysis, first of a single stringer, then of the stiffened panel under compressive load, provided results in good agreement with the experimental ones. The analyses were performed taking into account either for the geometric non-linearity associated with the large deformations of the structures under the action of compressive loads either for the local buckling of the flanges composing the stringers. Experimental activities were aimed at the characterization of the adopted materials with a special focus on the determination of buckling loads either of an L-shaped stringer either of a panel stiffened with four stingers. In both cases an excellent structural behaviour was shown, the panel and a single stringer being able to take huge loads after the first buckling appeared. The panel, in particular, showed an excellent post-buckling strength and broke by buckling failure of stringers. The welded interfaces did not fail indicating that thermoplastic welding is a suitable technique for assembly composite structural elements.